Pifmi Model Practice in Physics Learning - Perdy Karuru (Budapest International Research and Critics University, 2022)
One of the efforts to improve the quality of learning is to develop a PIFMI model (Multi-Interaction Oriented Physics learning) to improve reasoning power that has met the theoretically valid criteria. As follow-up research, it is necessary to test the PIFMI model in the field. Therefore, the purpose of this study is to determine the practicality of the PIFMI model in learning. This research method is development research. The results discussed in this study are focused on the results of field trials which are part of the development of the PIFMI model. From the results of field trials, suggestions were obtained for revising teaching materials, student worksheets, and adding activities to the PIFMI model syntax. The results of the expanded trial showed that the teacher and student assessments of the PIFMI model had met the practical criteria, and were practically used by teachers in managing and implementing learning, as well as being able to actively involve students during learning. In addition, the advantages of the PIFMI model obtained in learning are that it can increase interactions between teachers and students, students and their friends, students with media/learning resources, students with their groups, and groups with other groups, and make learning centered on participants. students, as well as being able to improve students' reasoning power and learning outcomes.